Kilka uwag na temat aktualnej recepcji literatury polskiej we Francji - Monluçon, Anne-Marie; Szeflińska-Baran, Magdalena (Czytanie Literatury. Łódzkie Studia Literaturoznawcze, 2014)
Various factors influence the contemporary reception of Polish literature in France. Economic criteria have succeeded ideological constraints, but new developments in the memory process in Poland and France also play a major role, all the more so as they are not synchronised, especially when it comes to the history of WW2 and Jewish-Polish relations. An analysis reveals the combination of at least four factors: the role of literary translations (re-editions and new translations), the results of historiographical research, the evolution of collective memory in both countries, as well as the interaction with foreign – mostly Anglo-Saxon – publications on the subject. Through a cursory presentation of the reception of Polish literature for youth and adults in the early 2000s, we intend to show that WW2 and Jewish-Polish relations, among other themes, occupy a central position. The two “re-enactments” of the figure of Jan Karski published in 2009 in French novels by Yannick Haenel and Bruno Tessarech and the ensuing polemic, as well as the re-edition of the testimony by the great Polish freedom fighter Jan Karski are a telling illustration of what is at stake in the contemporary reception of Polish literature in France and, more generally, of all the issues regarding that country.